Closed reduction and intramedullary nails for acute completely displaced femoral diaphysis fracture in children aged 2–6 - Qiao, Fei; Shang, Xinpeng; Jiang, Fei (Frontiers in Pediatrics, 2024)
Background: The purpose of this study was to assess the results of closed reduction and elastic stable intramedullary nail (ESIN) fixation in completely displaced fractures of the femoral diaphysis in children in this age group.Methods: A retrospective review of all children with acute completely displaced fractures of the femoral diaphysis in children aged 2 to 6 years treated from 2013 to 2020 was performed. A total of 34 patients were treated who met the inclusion criteria: Group 1: 21 fractures (transverse and short oblique); Group 2: 13 fractures (long oblique and spiral) that underwent closed reduction and elastic stable intramedullary nail (ESIN) fixation. No differences existed between the 2 groups with respect to age, extremity, sex, time to treatment, mechanism of injury, or fracture displacement. Demographic characteristics and radiographs were reviewed, and the following parameters were documented: surgery time, time to union, return to activities, range of motion of knee joints, and complications. .Results: Thirty-four children with acute completely displaced fractures of the femoral diaphysis were included: Group 1: 21 fractures; Group 2: 13 fractures. The patients included 15 girls (44.1%) and 19 boys (55.9%), with an average age of 4.4 years (range 2.8 to 6.5 years). The demographic characteristics did not differ between the two groups of patients. Overall, successful closed reduction and elastic stable intramedullary nail (ESIN) fixation could be achieved in all 34 patients. The mean surgical time was 40.4 and 43.0 min in Group 1 and Group 2, respectively (p=0.857). Fluoroscopy time was not significantly different between the two groups (37.0 versus 36.1 s, respectively; p=0.247).Cosmetic results were described as good and satisfactory by all patients. There were no refractures and no incidences of nonunion or growth arrest in the proximal epiphysis. Only two patients suffered from a superficial infection, which was resolved after the pins were shortened and oral antibiotics were administered. Conclusion: Closed reduction and elastic stable intramedullary nail (ESIN) fixation can be successfully used to treat completely displaced fractures of the femoral diaphysis in children aged two to six years.